KAJIAN PENILAIAN BAHAYA TANAH LONGSOR PROVINSI SUMATERA UTARA - kurniawan, lilik (Jurnal Sains dan Teknologi Indonesia, 2008)
Landslide assessment is the process by which decision-makers begin to bring order to the chaos that result from a disaster. Landslide hazard zonation helps in identifyingstrategic points and geographically critical areas prone to landslides. Landslide hazard zonation map was prepared by integrating the effect of various triggering factors. Conditions of geomorphology, hydrogeology, soil types and their distribution, and also current landuse are considered as supported data. Zonation mapin Sumatera Utara Province was divided into four zones of landslide : zone of very low susceptibility to landslide 16.164,76 km2, zone of low susceptibility to landslide 33.166,54 km2, zone of moderate susceptibility to landslide 20.120,47 km2, zone of high susceptibility to landslide 401,89 km2. Tapanuli Selatan region has widest zone of high susceptibility to landslide 8,3 km2.